1975
DOI: 10.1002/star.19750270404
|View full text |Cite
|
Sign up to set email alerts
|

A Pulsed NMR Study of Some Aspects of Starch Gelatinization

Abstract: Spin‐spin relaxation times of protons in starch suspensions are reported. Values were found to change markedly upon gelatinization. This behaviour is attributed to an increase in the mobility and hydration of polymer chains. It is suggested that the change in relaxation time reflects the properties of a small number of protons in the system and that the bulk of the water is not bound in any fundamental sense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…The 'H NMR relaxations (TI and T2) were characterized by a single time constant indicating that a two-state model with fast exchange may be adequately accounting for such observations. This model was also proposed by Leliiijre et al [27] for wheat starch-water suspensions up to 40% starch based on T2 measurements.…”
Section: Introductionmentioning
confidence: 67%
“…The 'H NMR relaxations (TI and T2) were characterized by a single time constant indicating that a two-state model with fast exchange may be adequately accounting for such observations. This model was also proposed by Leliiijre et al [27] for wheat starch-water suspensions up to 40% starch based on T2 measurements.…”
Section: Introductionmentioning
confidence: 67%
“…However, since the bulk water in the starch suspension is absorbed by the starch after heating, the mobility of water should be decreased. Using pulsed NMR, Lelievre and Mitchell (1975) studied starch gelatinization and found that, when the temperature of a starch suspension was increased, water mobility was decreased, indicating the adsorption of water to starch molecules. Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…Minimally, gelatinization entails (1) the loss of crystallinity of the granule as measured by the loss of birefringence and its x-ray diffraction pattern13; (2) an uptake of heat as the conformation of the starch is altered14; and (3) hydration of the starch, accompanied by swelling of the granule15 and a decrease in the relaxation time of the water molecules. 16 These processes usually take place simultaneously, or nearly so. However, under certain conditions of temperature and water activity, a relatively small loss of crystallinity can be accompanied by a substantial amount of hydration.17 Biopolymers The swelling of starch and the gelatinization phase transition have been studied as a function of the degree of crosslinking introduced into starch gran~1es.l~ The loss of birefringence has been determined as a function of water content over a limited temperature range.…”
Section: Introductionmentioning
confidence: 99%